The Meritocracy as the Basic Paradigm of Public Space: According to an Ottoman â€˜Intellectualâ€™ Mustafa Ali (1541-1600) - Yanar, Omur (European Scientific Journal, ESJ, 2017)
The social functions consisting of principles such as â€œbeing able to embody, express and represent a message, a view, an attitude, a philosophy or an opinionâ€ are basic criterion of being intellectual. From this point of view, it is possible to say that every country, every age, every class, every ideology has suitable intellectuals for its structure. For this reason, the intellectual can not be assessed as a creation of modernity, that is, monopoly of a certain time and society. In parallel to the social functions of the intellectuals, Mustafa Ali who came to prominence as a creation of socio-political and economic conditions of the Ottoman State in the 16th century. Despite the monarchic and autocratic character of the Ottoman State, Mustafa Ali who revealed a paradigm about state and society life, not only at a theoretical level but also in a practical context, above all, exhibited an intellectual attitude with a critical, sharp, brave language and style. One of the most important determinations of Mustafa Ali about the Ottoman state and society life is erosion of meritocratic management mentality which ideally based superiority of the individual and talents of persons. Mustafa Ali, who regarded the erosion of the meritocracy as one of the most basic management problems, built his paradigm about state and society on this basis with examples of stories from near and distant pasts as well as religious references such as verse and hadith. In spite of the quantity of studies based on different aspects of Mustafa Ali, the absence of a study in a special sense on the basis of his emphasis of intellectuality and his demand of meritocracy which has vital values in the state and society at every stage of the historical process made it essential to carry out such a study.